Case report: Fatal poisoning caused by additive effects of two barbiturates - Takei, Sella; Kinoshita, Hiroshi; Jamal, Mostofa; Kumihashi, Mitsuru; Yamashita, Tadayoshi; Tanaka, Etsuko; Kawahara, Sachiko; Abe, Hiroko; Tsutsui, Kunihiko; Kimura, Shoji (Frontiers in Pharmacology, 2023)
A case of fatal poisoning involving multiple psychotropic drugs is presented. Quantitative toxicological analysis showed femoral blood concentrations of pentobarbital, phenobarbital, duloxetine, acetaminophen and tramadol were 10.39 µg/ml, 22.57 µg/ml, 0.22 µg/ml, 0.61 µg/ml and 0.22 µg/mL, respectively. We concluded that the death was due to the additive effects of two barbiturates. As both pentobarbital and phenobarbital act on gamma-aminobutyric acid (GABA) receptors, central nervous system activity was suppressed, causing respiratory depression. Additive pharmacological effects should be considered in cases of massive ingestion of multiple drugs.